2008
DOI: 10.1007/s10812-008-9073-y
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of thulium-activated cubic boron nitride

Abstract: UDC (535.37+543.42):548Under high pressure and temperature conditions, we have obtained samples of thulium-activated cubic boron nitride in the form of micropowders, ceramics, and polycrystals activated by thulium in the presence of aluminum. We studied the cathodoluminescence (CL), photoluminescence (PL), and photoluminescence excitation spectra of the samples. In the luminescence spectra we observe structured bands with maxima at ~370, ~475, 660, and ~800 nm, assigned to electronic transitions in the tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…1 During syntheses, defects and coexistent elements are often incorporated into c-BN and behave as the origin of various properties. It has been reported that c-BN shows both n-and p-type conductivity, 2,3 ultraviolet light emission from its p-n junction, 4 and luminescence, [5][6][7][8] for example.…”
Section: Introductionmentioning
confidence: 99%
“…1 During syntheses, defects and coexistent elements are often incorporated into c-BN and behave as the origin of various properties. It has been reported that c-BN shows both n-and p-type conductivity, 2,3 ultraviolet light emission from its p-n junction, 4 and luminescence, [5][6][7][8] for example.…”
Section: Introductionmentioning
confidence: 99%